2010
DOI: 10.1136/jcp.2009.065821
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in glycated haemoglobin between white subjects and those of South Asian origin with normal glucose tolerance: Table 1

Abstract: In subjects with similar fasting and postprandial glycaemia on OGTT, those of South Asian origin have higher HbA(1c) levels than white subjects. It is speculated that the higher glycaemia-independent HBA(1c) levels in people of South Asian origin could possibly contribute to their increase cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
(14 reference statements)
2
19
1
Order By: Relevance
“…This suggests that prediabetes may be a less useful clinical indicator of overall CVD risk in this group, congruent with both the findings of our model discrimination analyses and concerns other authors have expressed 6. Explanations for this difference for HbA 1c ‐based prediabetes may lie in the greater proportions identified by this measure in these ethnic groups; that is, there is less of a differential, in terms of cardiometabolic profile, between individuals with normoglycaemia and those with prediabetes, although obviously this does not apply to OGTT‐identified individuals with prediabetes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that prediabetes may be a less useful clinical indicator of overall CVD risk in this group, congruent with both the findings of our model discrimination analyses and concerns other authors have expressed 6. Explanations for this difference for HbA 1c ‐based prediabetes may lie in the greater proportions identified by this measure in these ethnic groups; that is, there is less of a differential, in terms of cardiometabolic profile, between individuals with normoglycaemia and those with prediabetes, although obviously this does not apply to OGTT‐identified individuals with prediabetes.…”
Section: Discussionsupporting
confidence: 92%
“…It is unclear how the greater prevalence of HbA 1c ‐identified prediabetes in this former group translates to cardiovascular risk, with some authors suggesting the HbA 1c definition of prediabetes may be less discriminative 6. As far as we are aware, this has never before been studied in South Asian populations; the majority of studies that have compared associations between prediabetes and cardiovascular disease by diagnostic criteria are in populations of European origin 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…. (Burden et al, 2009;Likhari et al, 2010). In addition, this independent effect of ethnicity in South Asians and White Europeans may exist for other markers of glycaemia as well, including FPG and 2-hour plasma glucose.…”
Section: Conclusion To Chaptermentioning
confidence: 99%
“…Key: BMI = body mass index, BP = blood pressure, FPG = fasting plasma glucose, PG = plasma glucose. There were many strengths of this analysis, including some improvements on previous reports (Selvin et al, 2011;Herman et al, 2007;Herman et al, 2009, Ziemer et al, 2010Saaddine et al, 2002;Burden et al, 2009;Likhari et al, 2010). The cohort size included large numbers of both White Europeans and South Asians allowing detection of any clinically significant differences.…”
Section: Effect Of Ethnicity On Acr and Glycaemic Markersmentioning
confidence: 99%
“…A small cross-sectional study 111 in 139 subjects -26% South Asian -found that South Asian origin was associated with higher HbA 1c levels than in white subjects (6.1% vs 5.9%, p = 0.02), even although the South Asians were younger and weighed less. There were no significant differences in FPG and 2-hour PG levels between the two groups.…”
Section: Ethnicity: South Asianmentioning
confidence: 99%